Assessment of the Role of Orexin A and Some Clinical Parameters in Children with Autism Spectrum Disorder - Sayer, Sarah (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2025)
Objective: Autism spectrum disorder [ASD] is characterized by impairments in emotional, social, and cognitive areas and is considered a neurodevelopmental disorder. These children often exhibit stereotypical and repetitive manners that may be inconsistent with their inner physiological cadence, leading to disturbances in the Wake-up and sleep cycle. This study aimed to investigate the serum Orexin A, 5-HT, glutamate, and oxidative stress status and compare the values with those of healthy controls. Methods: This study included 40 participants, 20 patients, and 20 controls. The samples of children with ASD were obtained from the AL-Shatra unit of Autism Care//Thi Qar. Children taking medication and those with neurological diseases were excluded from the study. Serum orexin A, 5-HT, glutamate, NO, and albumen levels were assessed in all participants. Results: The means of serum orexin A, 5-HT, glutamate, and NO levels of patients with ASD were significantly higher than those of the control group (p <0.05). However, serum GSH and albumen levels were lower among the cases than the control group (p < 0.05). Conclusion: orexin A, 5-HT, and glutamate measurements taken together may even be utilized as markers for the development of sleep and eating disorders and insomnia. The rising levels of orexin A in uncontrolled autism spectrum disorder may be a cause of rising BMI. This assessment may be beneficial in developing an appropriate treatment plan for these children. This assessment may be instrumental in developing an appropriate treatment plan for these children and may form the basis for developing and directing targeted treatment in the future.